1924-1949 yılları arasında din eğitimine yönelik yayınlanan eserlerin değerlendirilmesi - Çoştu, Kamil (My University, 2015)
yayın, lâiklik, din dersleri, yasaklanan eserler ÖZET 1924 yılında kabul edilen Tevhîd-i Tedrîsât ile birlikte Türk eğitim sistemi köklü bir değişim geçirmiştir. Bu kanunda din eğitimi-öğretimine yönelik de önemli maddeler yer almıştır. İlgili kanun sonrasında yapılan değişikliklerle din dersi kademeli olarak okullardan kaldırılmıştır. Kurumsal din eğitimi-öğretimi alanında yaşanılan gelişme, bu alandaki neşriyatçılığı derinden etkilemiştir. 1931 yılında kabul edilen Matbuat Kanunu da dinî içerikli yayınları olumsuz etkileyen bir diğer düzenlemedir. Bu kanun sonrasında din ve din eğitimine yönelik çeşitli yayınlar ilgisiz bir madde öne sürülerek yasaklanmıştır. Din derslerinin yapıldığı yıllar olan 1924-1930 arasında din eğitimi-öğretimine yönelik yayınlar daha çok resmî kurumlar tarafından neşredilmiştir. 1930-1949 arasında ise, bu alana yönelik yayınlar, resmî kurumlarca değil, daha çok bazı şahısların özel gayretleri ile hazırlanmıştır. Din eğitimi-öğretimine yönelik yayın ihtiyacının farkında olan Diyanet İşleri Başkanlığı, ilgili alanda 1930 öncesinde olduğu gibi sonrasında da önemli eserler yayımlamıştır. Kurumun neşrettiği yayınlar arasında Ahmet Hamdi Akseki’nin eserleri en önemli neşriyatlardandır.

I was born in İskilip/ Çorum in 1980. I completed my primary and secondary education in İskilip. In 2000 I started religious culture and moral knowledge teaching department in faculty of theology, Marmara University. I started working (serving) as an imam in January 2001 and still continue working in Salacak Fatih Mosque, to which I was first assigned in 2005. I finished my graduate education in February 2005. In the same year I started my Masters programme in Marmara University faculty of theology, religious culture and moral knowledge teaching department. I finished my Masters programme in 2007. The title of my thesis is “Social-culturel Structure of Street Children (The Istanbul Example)”. I did my military service in 2009. In 2009–2010 academic year, I started my Phd. programme in religious education department of the same faculty. Under the supervision of Prof. Dr. M. Faruk BAYRAKTAR I completed my PhD. The title of my thesis research is “Evaluation of the Books Published Between 1924 and 1949 Concerning Religious Education”. I have made presentations in various symposiums organized by Directorate of Religious Affairs, Marmara Üniversity Faculty of Theology and Ensar Foundation. Between July 2008 and February 2015, I gave religious culture and moral knowledge and Quran lessons in Üsküdar Paşakapısı Penal Institution. I also held office in the editorial board of “Din ve Hayat” magazine published by Istanbul Office of Mufti for a while. I am married and father of two sons.
Keywords: Din eğitimi; Eğitim; Tarih; Türkiye